2012
DOI: 10.1097/gme.0b013e318260143d
|View full text |Cite
|
Sign up to set email alerts
|

Successful teriparatide treatment of atypical fracture after long-term use of alendronate without surgical procedure in a postmenopausal woman

Abstract: Even though a previous study has reported that teriparatide healed stress fractures in a rat model and even with the time course of fracture healing in our patient, we are still not certain that teriparatide played a primary role in the positive response to therapy. Vitamin D therapy, calcium, and alendronate discontinuation may have played secondary roles. This case report may serve to introduce a direction for future research into the pharmacological treatment of atypical femoral fractures. Surgical treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
30
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 28 publications
1
30
0
Order By: Relevance
“…When beaking is detected in the contralateral side, the recent ASBMR Task Force guidelines recommend ceasing bisphosphonate, the evaluation of calcium and vitamin D with supplementation in the case of insufficiency (deficiency), and intramedullary nailing if pain persists in the beaking site (12). Some Authors have indicated that teriparatide is effective (13,14). In our case, bisphosphonate was ceased immediately after the contralateral subtrochanteric fracture, and vitamin D therapy was initiated for her vitamin D deficiency.…”
Section: Discussionmentioning
confidence: 91%
“…When beaking is detected in the contralateral side, the recent ASBMR Task Force guidelines recommend ceasing bisphosphonate, the evaluation of calcium and vitamin D with supplementation in the case of insufficiency (deficiency), and intramedullary nailing if pain persists in the beaking site (12). Some Authors have indicated that teriparatide is effective (13,14). In our case, bisphosphonate was ceased immediately after the contralateral subtrochanteric fracture, and vitamin D therapy was initiated for her vitamin D deficiency.…”
Section: Discussionmentioning
confidence: 91%
“…Several cases have been reported in the literature where TPP had been used to treat incomplete or complete AFF (Table 2) [3][4][5][6][7][8]; however, none of them showed the effect of TPP on reducing the cortical thickening. We hereby presented a case of preventing near AFF with clinical symptoms; cortical thickness; no obvious radiographic radiolucent line and bone marrow edema by reducing cortical thickness with TPP use.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is inconsistent evidence that teriparatide may advance healing of AFFs (8,14). Few publications report fracture healing with teriparatide when there is no recovery with conservative therapy (14,16). Saleh et al (14) pointed out that the presence of a radiolucent line in an incomplete fracture poses a high risk of progression to a complete fracture.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, the treatment of AFF is based on post-fracture approaches and there are few studies on incomplete AFF treatment (16). Discontinuation of the antiresorptive agent and supplementation of vitamin D and calcium are general suggestions.…”
Section: Discussionmentioning
confidence: 99%